2020
DOI: 10.3389/fgene.2020.00093
|View full text |Cite
|
Sign up to set email alerts
|

The Oncogenic and Tumor Suppressive Functions of the Long Noncoding RNA MALAT1: An Emerging Controversy

Abstract: Long noncoding RNAs are recently emerging as critical factors of tumorigenesis. Originally regarded as a pre-messenger RNA (mRNA) splicing regulator, the long noncoding RNA MALAT1 has been demonstrated to regulate gene transcription by binding histone modification enzymes and transcription factors, and to regulate mRNA and protein expression post-transcriptionally by binding microRNAs (miRNAs) and acting as a sponge. Early studies consistently report that MALAT1 is up-regulated in human cancer tissues of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 81 publications
1
63
1
1
Order By: Relevance
“…While the study was performed in a different cancer model, the results are exactly opposite of ours. It looks like that MALAT1 might have different effects in different cancers but still such contrasting observations 38 make it important to comprehensively evaluate the role of MALAT1 before advancing the findings further in the clinics.…”
Section: Discussionmentioning
confidence: 99%
“…While the study was performed in a different cancer model, the results are exactly opposite of ours. It looks like that MALAT1 might have different effects in different cancers but still such contrasting observations 38 make it important to comprehensively evaluate the role of MALAT1 before advancing the findings further in the clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that lncRNAs are emerging as important regulators of cancer initiation, maintenance, and progression, attracting great attention. 14 Many dysregulated lncRNAs have been identified in human cancers, such as the well-characterized MALAT1, 15 H19 16 , HOTAIR, 17 and ANRIL 18 and so on. In the present study, we found a breast cancer-related lncRNA, IGF2-AS, which was significantly decreased in human breast cancer tissues, cells, as well as plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, functional experiments both in vivo and in vitro demonstrated that lnc-HSD17B11-1:1 significantly promoted proliferation and metastatic abilities of CRC cells, while knockdown of lnc-HSD17B11-1:1 showed an inverse effect. A growing body of research suggests that some lncRNAs could serve as sponges for miRNAs to regulate the expression of target mRNA in CRC (Chen et al, 2020a). For instance, LINC00461 may be an oncogene in CRC by targeting miR-323b-3p through NFIB signaling pathway (Yu et al, 2019), Moreover, lncRNA MIR4435-2HG was reported to play an oncogenic role by promoting CRC growth and metastasis and establish the presence of MIR4435-2HG/miR-206/YAP1 axis in CRC (Dong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%